Chennakeshava temple, Beluru, The Vamana avatar and the Varaha avatar, p25 - Brig Ajai Singh (2021)
Image courtesy: Brig A.P. Singh - www.collectingmoments.in; Image courtesy: Brig A.P. Singh - www.collectingmoments.in